Determination of clinical biologic width in chronic generalized periodontitis and healthy periodontium: A clinico-radiographical study - Reetika Gaddale; Jayashree Mudda; Ilangovan Karthikeyan; Shrikar Desai; Harshada Hemchandra Shinde; Roopali Tapashetti (Wolters Kluwer Medknow Publications, 2015)
Background: The dimensions of dentogingival junction have been evaluated from autopsy jaw specimens. Previous studies demonstrated variability in histologic biologic width (BW) in periodontal health and mild periodontitis. Few studies have been done on the measurement of clinical BW in periodontitis. BW variation provides implications for selection of surgical or nonsurgical approaches. The purpose of this study was to determine clinical BW in periodontal health and chronic generalized periodontitis and to compare it with histologic dimensions of BW. Materials and Methods: A total of 20 subjects with chronic generalized periodontitis and 20 subjects with healthy periodontium were included in the present study. Plaque index and community periodontal index of treatment needs were scored; moreover, probing depth (PD) and clinical attachment level were measured. Full mouth intraoral periapical radiographs were taken, and digitalized images were obtained to measure the crestal bone level using computerized software. Results: Clinical BW was significantly greater in both healthy and periodontitis groups than previously reported histologic BW of 2.04 mm (P < 0.001). The mean clinical BW was 3.98 mm. Conclusion: Mean clinical BW in both groups was significantly greater than histologic BW and sites with shallow PDs demonstrated greatest BW, suggesting that these sites may be at increased risk for losing significant attachment during surgical procedures.